The Blessed Antonio (Patrizi) from Monticiano, Sienna (Italy): Bioanthropological and Palaeohistological Considerations - Piombino-Mascali, Dario; Zink, Albert; Maixner, Frank (Acta medica Lituanica, 2022)
Background: A medieval mummy known as the Blessed Antonio (Patrizi) is held in the church of Saints Peter and Paul at Monticiano, Sienna, central Italy. Objectives: The aim of our investigation was to complete a biological profile of the subject, as well as to assess the impact of deterioration to the concerned remains. Methods: As a follow-up of our bioanthropological, macroscopic approach, two of the samples taken underwent rehydration, fixation, desiccation, paraffin-embedding, and staining according to standard histological techniques applied to mummified remains. Results: The body was determined to be that of an adult male, who showed some pathological changes such as dental calculus and what is suspected to be hallux valgus. The overall preservation of a skin sample revealed damage caused by a post-mortem infestation of insects, while a second, inner sample was identified as lung tissue, and revealed a case of anthracosis. Conclusions: The Blessed Antonio was an adult male, who had poor dental hygiene and was likely exposed to smoke during his lifetime. Damage observed on the remains indicated that a conservation treatment was desirable for the future preservation of the body.